GERIATRIC PATIENT WITH DELIRIUM PROFILE IN SAIFUL ANWAR GENERAL HOSPITAL MALANG FROM JANUARY 2005 UNTIL JUNE 2010 - Sunarti, Sri; Rahayu, Masruroh; Desetyaputra, Dimas Ryan (Malang Neurology Journal, 2015)
Background. Delirium is a serious health problem and the most frequent complaints in geriatric patients. Objective. This research aims to analyzes the patient profile and the underlying disease of delirum by using descriptive study and survey methods. Methods. Subjects were geriatric patients with age >60 years old diagnosed with delirium.Results. Patients with delirium syndrome was male sex 58.3% and female sex 41,7%, the highest age group between 60-65 years was 31.7% and 66-70 years was 30%, education is the senior high school level of 41.7% and junior high school level of 35%. Temperature delirium patients that >37.5oC (61.7%) patients and GCS due to moderate state was 100% patients. Hb and PCV were below normal at 71.7% and 70%. Conditions out of the hospital patients delirum syndrome is to live for 71.7%. The most underlying disease delirium syndrome were CVA 56.7%, Diabetes Melitus type II 23,3% and Sepsis 8,3%. Conclusion. The factors underlying the occurrence of delirium syndrome are male sex, aged 60-65 years old, low education, temperatures above normal, decreased consciousness, low PCV, anemia and most diseases that cause delirium syndrome is CVA, Diabetes Melitus type II and Sepsis.